Cyclization of Nitroacetamide Derivatives with a Tethered Phenyl Ring in Triflic Acid - Fanté, Bamba; Soro, Yaya; Siaka, Sorho; Marrot, Jérôme; Coustard, Jean-Marie (Synlett, 2014)
N-(3-Hydroxypropyl)-2-nitro-N-(ω-phenylalkyl)acetami-des underwent intramolecular cyclization in triflic acid to afford the corresponding hydroxyimino six- to nine-membered benzofused lactams. The six-membered derivative slowly transformed into 2-(3-hydroxypropyl)isoquinolin-3-one. NMR spectroscopic analysis in situ provided information on the cationic species involved in the reaction, permitting a mechanism to be postulated. This reaction provides a novel and simple route to benzofused lactams.
Keywords: cations; protonation; cyclization; lactams; bicyclic compounds